Calcium in the mineral nutrition of yellow passion fruit cultivated in lined pits and with saline water - Marlene A. F. Bezerra; Lourival F. Cavalcante; Francisco T. C. Bezerra; Walter E. Pereira; Flaviano F. de Oliveira; Aldeir R. Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Nutritional status is an important tool in salinity management, because salt stress interferes with both the absorption and the assimilation of mineral nutrients by plants. The objectives of this experiment were to evaluate the effects of water salinity, lateral protection of pits against water losses and calcium doses on the leaf concentration of macronutrients and sodium of yellow passion fruit cv. BRS GA1. The treatments were arranged in a randomized block design in split plots in a 2 × (2 × 5) factorial scheme, corresponding to water salinity (0.3 and 4.0 dS m-1) in the main plot, and the combinations between lateral protection of pits (without and with) and calcium doses (0, 30, 60, 90 and 120 kg ha-1) in the subplots. Leaf concentrations of macronutrients and sodium were determined at the phenological stage of full flowering. Irrigation of yellow passion fruit with 4.0 dS m-1 water decreased the leaf concentrations of macronutrients. The lining of the pits compromised macronutrient concentration in the plants. Calcium fertilization is recommended for yellow passion fruit cultivated in Entisol with low calcium concentration at the dose of 60 kg ha-1, because it raises nitrogen and calcium concentrations in plants irrigated with non-saline water and magnesium and sulfur concentrations in those irrigated with saline water. Calcium attenuates salt stress because it promotes the accumulation of macronutrients in yellow passion fruit under saline conditions.